Discovery of MAGL Inhibition by Lophine Derivatives: An Unexpected Finding from Chemiluminescent Assay Development - Roberta Ottria; Silvana Casati; Ornella Xynomilakis; Aleksandar Veselinović; Pierangela Ciuffreda (Molecules)
The inhibitory effects of two novel lophine derivatives were unexpectedly discovered during the development of a chemiluminescent monoacylglycerol lipase (MAGL) assay. The proposed lophine derivatives were found to exhibit concentration-dependent inhibitory effects on MAGL with the octanoic and palmitic acid esters of 2-(4-hydroxyphenyl)-4,5-diphenylimidazole showing the strongest activity. Reversibility assays using a fluorometric method confirmed that these compounds interact with MAGL in a stable, irreversible manner. To further investigate their mode of interaction, docking studies were performed, supporting the hypothesis that compounds 3 and 4 may act as competitive and irreversible inhibitors. Lophine derivatives were initially designed and synthesized as potential chemiluminescence pro-enhancers. However, assay optimization revealed no signal production upon MAGL hydrolysis, precluding their use as chemiluminescent probes. These findings suggest that lophine is a promising candidate for the development of MAGL inhibitors, although further optimization is needed to enhance binding affinity and selectivity.